A comprehensive review of IgG4-related pancreatitis: pathogenesis, diagnosis, and therapeutic advances - Wu, Siqin; Qin, Xiaowen; Jin, Zhenjing; Yang, Lanlan (Frontiers in Immunology, 2025)
IgG4-related pancreatitis (IRP) is a form of chronic pancreatitis characterized by the infiltration of IgG4-positive plasma cells, representing a pancreatic manifestation of IgG4-related disease (IgG4-RD). In recent years, with the growing understanding of IgG4-RD, the incidence of IRP has shown an increasing trend. This article provides a comprehensive review of the latest advancements in the epidemiology, etiology, pathogenesis, clinical manifestations, diagnosis, differential diagnosis, and treatment of IRP.